ANALYSIS OF THE INTERNAL CONTROL SYSTEM FOR FIXED ASSETS AT THE DEPARTMENT OF INDUSTRY, TRADE, ENERGY AND MINERAL RESOURCES OF NORTH SUMATRA PROVINCE - Dito Aditia Darma Nasution; Diva Maulidia; Nurhidayah Dalimunthe; Reva Putri Arihan; Bella Viona Sitompul (International Journal of Management, Economic and Accounting, 2025)
This study aims to determine whether the internal control system for fixed assets at the North Sumatra Provincial Office of Industry, Trade, Energy, and Mineral Resources complies with the components of the internal control system according to Government Regulation No. 60 of 2008. The types of data used are primary and secondary data. Data collection techniques were carried out through observation, interviews, and documentation. The data was analyzed using qualitative descriptive methods. The results of the study indicate that the implementation of the internal control system for fixed assets at the North Sumatra Provincial Office of Industry, Trade, Energy and Mineral Resources is in accordance with the components of the internal control system as stipulated in Government Regulation No. 60 of 2008, except for the control activities component of the physical control subcomponent of assets, the risk assessment component, and the monitoring component, which still have weaknesses such as asset loss and damage due to the lack of optimal physical supervision of assets.